SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU BANGUNAN BERBASIS WEB (Jurnal Riset Manajemen dan Akuntansi, 2023)
PT. Bintang Mataram Sejahtera Semarang is a company engaged in the field of housing construction contractors. In carrying out its business, the company has a project warehouse near the project that is being worked on for storage of materials while working on the project, the project warehouse is located to move according to the project being worked on. The problem faced is that the recording of material inventory is still done manually using the goods control stock card then after it is recorded it is entered into Microsoft Excel, this causes a long time for recording material data stocks because you have to open the parts one by one or sheet per sheet beforehand to make reports. and can hinder reporting to company leaders.This study aims to produce a system that can speed up the process of recording inventory of building material stock in the construction project warehouse, and can generate various material inventory reports that can control the availability of material inventory in the project warehouse. The method used is the Perpetual Inventory System, namely material management is carried out by controlling the stock of material inventory directly per period continuously updating the stock every time material comes in and material goes out. A web-based building material inventory information system with the PHP programming language and supported by MySQL database storage is urgently needed to assist administration, foremen and project leaders to speed up various material inventory control reports that are fast, accurate and thorough and can improve officer performance in presenting report.